Improved thermoelectric transport properties of Cu1.8S with NH4Cl-derived mesoscale-pores and point-defects. Issue 15 (15th November 2016) - Yao, Yao; Zhang, Bo-Ping; Pei, Jun; Han, Ye-Mao; Zhou, Min
Abstract: In the present work, we have investigated the effect of NH4 Cl content ( x ) on the microstructure, phase structure and thermoelectric transport properties of Cu1.8 S- x NH4 Cl ( x =0, 1, 5, 10, 15 wt%) bulks fabricated by combining mechanical alloying and spark plasma sintering. The addition of NH4 Cl introduces lots of mesoscale (0.1–2.0 µm) pores and point-defects such as V S, C l S, C l i ' and H i, leading to a decreased carrier mobility and an increased carrier concentration, respectively. As a result, the thermal conductivity was effectively reduced from 2.1 to 1.2 W m −1 K −1 as increasing x from 0 to 10 wt% at 673 K. A peak ZT value of 0.3 was achieved at 673 K for x =1 wt% resulted from a low thermal conductivity of 1.6 W m −1 K −1 combining an appropriate power factor of 717 μWm −1 K −2, which is 15% higher than that (0.26) of pristine Cu1.8 S. Our result indicates that the introduction of NH4 Cl in thermoelectric materials is an effective and convenient strategy to improve ZT by decreasing thermal conductivity.